The Rh-1 Full-Size Humanoid Robot: Design, Walking Pattern Generation and Control - M. Arbulú; D. Kaynov; L. Cabas; C. Balaguer (Applied Bionics and Biomechanics)
This paper is an overview of the humanoid robot Rh-1, the second phase of the Rh project, which was launched by the Robotics Lab at the Carlos III University of Madrid in 2002. The robot mechanical design includes the specifications development in order to construct a platform, which is capable of stable biped walking. At first, the robots’ weights were calculated in order to obtain the inverse dynamics and to select the actuators. After that, mechanical specifications were introduced in order to verify the robot’s structural behaviour with different experimental gaits. In addition, an important aspect is the joints design when their axes are crossed, which is called ‘Joints of Rectangular Axes’ (JRA). The problem with these joints is obtaining two or more degrees of freedom (DOF) in small space. The construction of a humanoid robot also includes the design of hardware and software architectures. The main advantage of the proposed hardware and software architectures is the use of standardised solutions frequently used in the automation industry and commercially available hardware components. It provides scalability, modularity and application of standardised interfaces and brings the design of the complex control system of the humanoid robot out of a closed laboratory to industry. Stable walking is the most essential ability for the humanoid robot. The three dimensional Linear Inverted Pendulum Model (3D-LIPM) and the Cart-table models had been used in order to achieve natural and dynamic biped walking. Humanoid dynamics is widely simplified by concentrating its mass in the centre of gravity (COG) and moving it following the natural inverted pendulum laws (3D-LIPM) or by controlling the cart motion (Cart-table model). An offline-calculated motion pattern does not guarantee the walking stability of the humanoid robot. Control architecture for the dynamic humanoid robot walking was developed, which is able to make online modifications of the motion patterns in order to adjust it to the continuously changing environment. Experimental results concerning biped locomotion of the Rh-1 humanoid robot are presented and discussed.